A saída do Reino Unido da União Europeia e sua influência no movimento separatista da Escócia (2010-2022) - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present work aims to analyze how the departure of the United Kingdom from the European Union created conditions for the strengthening of the separatist movement in Scotland, during the period from 2010 to 2022. Fostered by the desire to become independent by the Scottish National Party, Scotland went through a referendum in 2014, questioning the Scottish people whether the nation should be independent or not. However, the percentage was that they should remain part of the UK, mainly because of the European Union; bloc that benefited the Scottish economy. In 2016, there was a referendum questioning whether or not the United Kingdom should continue to be a member of the European Union, resulting in the desire of the population to leave. With the UK leaving the European Union officially in 2020, the separatist movement in Scotland began to gain strength. The work uses the principle of self-determination of peoples, of International Law, to promote the right that the Scottish nation must have to guarantee its democracy and the right to choose, to self-govern. It is shown that the departure of the United Kingdom from the European Union created conditions for the strengthening of the Scottish separatist movement through the possibility of creating a new referendum, for the population to decide whether or not it wants to remain part of the country. Despite attempts to make it happen, the United Kingdom acts as an obstacle for the referent to occur again. The research was carried out using the qualitative method, seeking to analyze a phenomenon that occurred during the given period, hypothetical-deductive, seeking to test the proposed hypothesis and having as a research level a historical investigation, collecting information that occurred in the past for a greater understanding in the present.
The UK's departure from the European Union and its influence on the Scottish separatist movement (2010-2022)
Keywords: Movimento separatista; Princípio de autodeterminação dos povos; Escócia; Reino Unido; Brexit; Separatist movement; Principle of self-determination; Scotland; United Kingdom; CNPQ::CIENCIAS SOCIAIS APLICADAS